2013
DOI: 10.3109/00498254.2013.835885
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide is metabolized by CYP2D6 and is a reversible inhibitor, but not inactivator, of CYP2D6

Abstract: Metoclopramide is a widely used clinical drug in a variety of medical settings with rare acute dystonic events reported. The aim of this study was to assess a previous report of inactivation of CYP2D6 by metoclopramide, to determine the contribution of various CYPs to metoclopramide metabolism, and to identify the mono-oxygenated products of metoclopramide metabolism. Metoclopramide interacted with CYP2D6 with Type I binding and a Ks value of 9.56 ± 1.09 μM. CYP2D6 was the major metabolizer of metoclopramide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…49 Ciprofloxacin is reportedly excreted via transintestinal excretion but not into bile. Only for tiotropium (CYP2D6, 3A4) 52 and metoclopramide (CYP2D6, 1A2, 2C9, 2C19, 3A4) 50 are the catabolizing enzymes, and for avibactam the involved organic anion transporters 53 known. Only for tiotropium (CYP2D6, 3A4) 52 and metoclopramide (CYP2D6, 1A2, 2C9, 2C19, 3A4) 50 are the catabolizing enzymes, and for avibactam the involved organic anion transporters 53 known.…”
Section: Available Datamentioning
confidence: 99%
“…49 Ciprofloxacin is reportedly excreted via transintestinal excretion but not into bile. Only for tiotropium (CYP2D6, 3A4) 52 and metoclopramide (CYP2D6, 1A2, 2C9, 2C19, 3A4) 50 are the catabolizing enzymes, and for avibactam the involved organic anion transporters 53 known. Only for tiotropium (CYP2D6, 3A4) 52 and metoclopramide (CYP2D6, 1A2, 2C9, 2C19, 3A4) 50 are the catabolizing enzymes, and for avibactam the involved organic anion transporters 53 known.…”
Section: Available Datamentioning
confidence: 99%
“…Several researches have indicated that the absorption of metoclopramide in small intestinal mucosa was mainly mediated by P-gp, and metoclopramide was mainly metabolized by CYP2D6. [19][20][21] Therefore, the potential drug-drug interaction of metoclopramide mediated by CYP450 and P-gp might happen.…”
Section: Discussionmentioning
confidence: 99%
“…In similar metabolism experiments with CYP3A4, mono-oxygenation of SCH 66712 at four different positions was apparent by the presence of four distinct m/z 355 ions in the mass spectral analysis (M+1). To determine whether mono-oxygenation was on carbon or nitrogen atoms, titanium trichloride (TiCl 3 ) was used to selectively reduce any hydroxylamines as previously described elsewhere (Seto and Guengerich, 1993;Kulanthaivel et al, 2004;Livezey et al, 2014). Because the metabolites formed by CYP3A4 and by CYP2D6 were the same, the metabolites as formed by CYP2D6 were used in the TiCl 3 experiments due to the more uniform distribution of products (as compared with CYP3A4) and therefore ease of comparison of changes upon HCl or TiCl 3 treatment (vide infra).…”
Section: Methodsmentioning
confidence: 99%
“…A control sample not treated with TiCl 3 or HCl was placed on ice for 1 hour. All samples were then centrifuged, and the supernatant was analyzed by LC-ESI-MS as described previously (Nagy et al, 2011;Livezey et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation